Use of soil fungi in the biosorption of three trace metals (Cd, Cu, Pb): promising candidates for treatment technology?. Issue 24 (27th October 2020) - Albert, Quentin; Baraud, Fabienne; Leleyter, Lydia; Lemoine, Mélanie; Heutte, Natacha; Rioult, Jean-Philippe; Sage, Lucile; Garon, David
ABSTRACT: Trace metal contamination is a widespread and complex environmental problem. Because fungi are capable of growing in adverse environments, several fungal species could have an interesting potential in remediation technologies for metal contaminated environments. This study proposes to test the ability to tolerate and biosorb three trace metals (Cd, Cu and Pb) of 28 fungal isolates collected from different soils. First, a tolerance assay in agar medium was performed. Each isolate was grown in the presence of Cd, Cu, and Pb at different concentrations. Then, we exposed each soil fungus to 50 mg L −1 of Cd, Cu, or Pb during 3 days in liquid medium. Parameters such as biomass production, pH, and biosorption were evaluated. The results showed that responses to metal exposure are very diverse even with fungi isolated from the same soil sample, or belonging to the same genera. Several isolates could be considered as good metal biosorbents and could be used in future mycoremediation studies. Among the 28 fungi tested, Absidia cylindrospora biosorbed more than 45% of Cd and Pb, Chaetomium atrobrunneum biosorbed more than 45% of Cd, Cu, Pb, and Coprinellus micaceus biosorbed 100% of Pb. GRAPHICAL ABSTRACT: UF0001